Keja L. Valens. Desire between Women in Caribbean Literature. New York: Palgrave Macmillan, 2013. vii + 214 pp. - Mary McCullough (Studies in 20th & 21st Century Literature, 2017)
Book Review of Keja L. Valens. Desire between Women in Caribbean Literature. New York: Palgrave Macmillan, 2013. vii + 214 pp.
Keywords: Women; Caribbean Literature; Francophone Literature; Hispanophone Literature; Anglophone Literature